“Dear Peers! Are You “Free to Learn” For Your Kin?” - Gupta, Deepak (Indian Journal of Community Health, 2019)
I have stories to tell. More than a decade ago and ironically almost a decade after my graduation from medical school, I trained and got certified in basic life support (BLS) skills because I did NOT want to fail my family, my friends and my patients as I had desired to NOT fail my conscience as a physician. I will tell you this that you will never regret honing BLS skills whenever you will see the smiles on the faces of revived and you will never forget when not forgiven – by else and/or by self – for your reluctance in knowing what’s expected from you especially as a physician. Even though my natural desire to hone BLS skills was born in the times when it was NOT mandated, my free will to care for my family, my friends and my patients had always brought me back to BLS training centers for revisiting my skills again and again, years after years. Essentially, I have recognized Brain-Heart-Lungs as the Trinity of Life and hereafter I plead to all my peers irrespective of which stage of career they are in: “Please hone your BLS skills, at least be a Heartsaver®, for your kin so that when your kin, your beloved, needs your help, you don’t delay providing help compared to leaving “To go find one”